Single Prolonged Stress Reduces Intrinsic Excitability and Excitatory Synaptic Drive Onto Pyramidal Neurons in the Infralimbic Prefrontal Cortex of Adult Male Rats - Nawreen, Nawshaba; Baccei, Mark L.; Herman, James P. (Frontiers in Cellular Neuroscience, 2021)
Post-traumatic stress disorder (PTSD) is a chronic, debilitating mental illness marked by abnormal fear responses and deficits in extinction of fear memories. The pathophysiology of PTSD is linked to decreased activation of the ventromedial prefrontal cortex (vmPFC). This study aims to investigate underlying functional changes in synaptic drive and intrinsic excitability of pyramidal neurons in the rodent homolog of the vmPFC, the infralimbic cortex (IL), following exposure to single prolonged stress (SPS), a paradigm that mimics core symptoms of PTSD in rats. Rats were exposed to SPS and allowed one week of recovery, following which brain slices containing the PFC were prepared for whole-cell patch clamp recordings from layer V pyramidal neurons in the IL. Our results indicate that SPS reduces spontaneous excitatory synaptic drive to pyramidal neurons. In addition, SPS decreases the intrinsic membrane excitability of IL PFC pyramidal cells, as indicated by an increase in rheobase, decrease in input resistance, hyperpolarization of resting membrane potential, and a reduction in repetitive firing rate. Our results suggest that SPS causes a lasting reduction in PFC activity, supporting a body of evidence linking traumatic stress with prefrontal hypoactivity.